2006
DOI: 10.1111/j.1439-0426.2006.00768.x
|View full text |Cite
|
Sign up to set email alerts
|

Length-weight relationships of an invasive cyprinid fish (Carassius gibelio) from 12 Greek lakes in relation to their trophic states

Abstract: The length-weight relationships of the cyprinid fish Carassius gibelio (Bloch, 1782) are described for the 12 most important lakes of Greece. Carassius gibelio is an allogynogenetic fish species, which was introduced into Greek lakes during the late 1970s. The values of the exponent b of the length-weight relationships ranged from 2.33 to 3.38, and varied with the trophic state of the lake. In eutrophic lakes these b values were significantly (P < 0.001) lower than in oligotrophic or mesotrophic lakes. Relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
85
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(93 citation statements)
references
References 16 publications
5
85
0
3
Order By: Relevance
“…Similar observations were mentioned by earlier workers from this region as well as from other researchers who stated that lengthweight relationship is influenced by physico-chemical (Sunder and Subla, 1984a;Weatherley and Gill, 1987). It has been reported that prevailing environmental conditions (Przybylski, 1996;Tsoumani et al, 2006) and intrinsic factors (Knaepkens et al, 2002) are related to the growth of fish. However, this speculation needs further investigation on other exotic as well as in endemic fish.…”
Section: Effect Of Physico-chemical Features On L-w Relationshipsupporting
confidence: 76%
See 1 more Smart Citation
“…Similar observations were mentioned by earlier workers from this region as well as from other researchers who stated that lengthweight relationship is influenced by physico-chemical (Sunder and Subla, 1984a;Weatherley and Gill, 1987). It has been reported that prevailing environmental conditions (Przybylski, 1996;Tsoumani et al, 2006) and intrinsic factors (Knaepkens et al, 2002) are related to the growth of fish. However, this speculation needs further investigation on other exotic as well as in endemic fish.…”
Section: Effect Of Physico-chemical Features On L-w Relationshipsupporting
confidence: 76%
“…There are also examples where researchers have compared biological parameters in different ecosystems (water bodies having different trophic status) in order to assess the influence of the environmental factors on fish growth. Tsoumani et al (2006), for example, compared the length-weight relationships of the cyprinid fish Carassius gibelio (Bloch, 1782) length-weight relationship. The fresh water bodies of the Kashmir Himalayas has got great commercial importance.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely considered as pest species in most European aquatic ecosystems (Kottelat 1997) due to gynogenetic reproduction (Fan and Shen 1990, Gui 1996, Zou et al 2001 and its flexible interspecific mating strategy for sperm exploitation ). This reproductive strategy and the antagonistic behaviour for food and space in spawning grounds have created visible negative effects on indigenous species and in trophic complexes in various ecosystems , Perdikaris et al 2005, Tsoumani et al 2006. On the other hand, common carp is a valuable fishery resource in many lakes in western and northern Greece.…”
mentioning
confidence: 99%
“…tions of the freshwater fishes in Greece have suffered either from a limited number of species investigated (Tsoumani et al 2006, Tsoumani et al 2013 or focused mainly on lake ecosystems (Kleanthidis et al 1999, Tsoumani et al 2006, Bobori et al 2010, and river ecosystems (Petriki et al 2011, Sapounidis et al 2011.…”
mentioning
confidence: 99%